Implementasi Penggunaan Game Stairs & Cigarettes terhadap Peningkatan Pemahaman Peserta Didik Sekolah Menengah Mengenai Bahaya Merokok - Khairiah, Nafisah; Makaria, Eklys Cheseda; Putro, Hendro Yulius Suryo (Paedagogie, 2026)
This study aims to analyze the extent to which the use of the educational game Stairs & Cigarettes can improve high school students' understanding of the dangers of smoking. This study uses a quantitative approach with a quasi-experimental One Group Pretest-Posttest Design. The subjects were 34 students of grades X-F of SMA Negeri 9 Banjarmasin who participated in classical guidance services. Data collection was carried out using a questionnaire on understanding the dangers of smoking given to students at the pretest stage to determine their initial level of understanding, then after being given treatment in the form of the educational game Stairs & Cigarettes, students were given a posttest to determine changes in understanding after the treatment. The research instrument was a questionnaire on understanding the dangers of smoking compiled based on the Health Belief Model indicators with 74 items that have been tested for validity and represent indicators of perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. Data were analyzed using descriptive statistics and paired sample t-test. The results showed that the average student understanding score increased from 265.09 in the pretest to 309.85 in the posttest. The results of the paired sample t-test showed a significance value of p<0.05, indicating a significant increase in student understanding after the treatment. Thus, it can be concluded that the use of the educational game Stairs & Cigarettes has a significant effect on increasing high school students' understanding of the dangers of smoking.